2014
DOI: 10.1161/jaha.113.000514
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Presentation of Carotid Sinus Hypersensitivity Is Associated With Impaired Cerebral Autoregulation

Abstract: BackgroundCarotid sinus hypersensitivity (CSH) is associated with syncope, unexplained falls, and drop attacks in older people but occurs asymptomatically in 35% of community‐dwelling elders. We hypothesized that impaired cerebral autoregulation is associated with the conversion of asymptomatic CSH to symptomatic CSH. We therefore conducted a case–control study evaluating individuals with CSH with and without the symptoms of syncope or unexplained falls, as well as non‐CSH controls, to determine whether the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Additionally, any etiology that causes hypotension might result in symptoms similar to those determined by CSH, with the first symptoms of retinal and cerebral hypoperfusion expected in the upright position when SBP drops below 80 mmHg. An association between impaired cerebral autoregulation and the symptomatic presentation of CSH was demonstrated by Tan et al 27 in a study using transcranial Doppler ultrasonography during lower body negative pressure-induced systemic hypotension. 27 They have demonstrated that individuals with symptomatic CSH have lower cerebral blood flow than do asymptomatic individuals with CSH in response to comparable reductions in systemic blood pressure, and have suggested that symptomatic individuals have an increased susceptibility to syncope or falls compared with individuals with asymptomatic CSH due to a lower ability to maintain cerebral blood flow in the face of a hypotensive challenge.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, any etiology that causes hypotension might result in symptoms similar to those determined by CSH, with the first symptoms of retinal and cerebral hypoperfusion expected in the upright position when SBP drops below 80 mmHg. An association between impaired cerebral autoregulation and the symptomatic presentation of CSH was demonstrated by Tan et al 27 in a study using transcranial Doppler ultrasonography during lower body negative pressure-induced systemic hypotension. 27 They have demonstrated that individuals with symptomatic CSH have lower cerebral blood flow than do asymptomatic individuals with CSH in response to comparable reductions in systemic blood pressure, and have suggested that symptomatic individuals have an increased susceptibility to syncope or falls compared with individuals with asymptomatic CSH due to a lower ability to maintain cerebral blood flow in the face of a hypotensive challenge.…”
Section: Discussionmentioning
confidence: 82%
“…However, the studies were small, uncontrolled, and provided no method of distinguishing cerebral autoregulatory derangements specific to carotid sinus stimulation from the effects of profound arterial hypotension, during which cerebral autoregulation falters and fails (60). We sought to overcome these limitations through a comparison of changes in cerebral autoregulation (as measured by TCD) in response to controlled lower body negative pressure-induced hypotension in subjects with CSS, those with asymptomatic CSH, and in healthy controls in a series of studies (61,62). In both studies, we found evidence of deranged cerebral autoregulation, in the first particularly through differences in cerebrovascular resistance and in the second in cerebral blood flow velocity between patients with CSS and controls (61,62).…”
Section: Is There a Pathophysiologic Rationale For Carotid Sinus Syndmentioning
confidence: 99%
“…We sought to overcome these limitations through a comparison of changes in cerebral autoregulation (as measured by TCD) in response to controlled lower body negative pressure-induced hypotension in subjects with CSS, those with asymptomatic CSH, and in healthy controls in a series of studies (61,62). In both studies, we found evidence of deranged cerebral autoregulation, in the first particularly through differences in cerebrovascular resistance and in the second in cerebral blood flow velocity between patients with CSS and controls (61,62). However, the findings have not been replicated elsewhere and suffer from the small sample sizes as well as the many limitations of the TCD method of estimating cerebral autoregulation.…”
Section: Is There a Pathophysiologic Rationale For Carotid Sinus Syndmentioning
confidence: 99%
“…In addition to CSH, hypotensive disorders such as vasovagal syncope (VVS) and orthostatic hypotension (OH) may be more common following stroke due to primary autonomic nervous system involvement [27], the adverse effects of medication or the presence of other related diseases such as diabetes. Furthermore, the presence of stroke disease will increase the likelihood of development of symptoms with CSH and OH, which often occurs asymptomatically among older adults with manifestation of symptoms once cerebral autoregulation is impaired [28]. In addition, the individual may not recall prodromal or syncopal symptoms from OH, VVS or CSH due to lack of awareness or amnesia for loss of consciousness [29,30,31].…”
Section: Risk Factorsmentioning
confidence: 99%